EKSPLORASI PRAKTIK BLENDED SOCIO-DIGITAL LEARNING DALAM MEMBANGUN AGENCY BELAJAR PADA SISWA - Ansori; Anggraini, Fatik Lutviana; Amrosy (Al-ATHFAL: Jurnal Pendidikan Anak, 2025)
Educational transformation through digital technology integration has created a need for learning models that are not only adaptive but also capable of building student learning agency. In this context, blended socio-digital learning (BSDL) is a strategic approach combining face-to-face learning with digitally-based social interaction. This exploratory qualitative study aims to: (1) describe teacher strategies in designing and implementing BSDL, (2) identify forms of student learning agency that emerge, and (3) understand contextual pedagogical and social factors. Data was collected through interviews, participatory observation, and digital documentation. The results show that combining social interaction with creative technology use encourages students to be more reflective, responsible, and active in designing their learning experiences. In conclusion, BSDL positively contributes to strengthening student learning agency, particularly in flexible and personalized learning contexts. It is recommended that teachers design strategies that integrate social and digital dimensions balancedly and provide space for students to take an active role. Keywords: learner agency; blended learning; socio-digital; elementary education; teacher strategies